Critical Evaluation of Article 24 of the Law on the Enforcement of Financial Sentences - Yasser Tak fallah; abolghasem morshedi (آموزه‌‌های فقه مدني, 2024)
Article 24 of the Law on the Enforcement of Financial Sentences specifies seven examples of debt exclusions; properties not liable to be distraint for debt, which the legislator has declared as non-seizable (seizure) and not subject to sale. The definition of properties not liable to be distraint for debt based on specific instances, due to the lack of a clear expurgated criterion, will give rise to numerous instances of ambiguity regarding applicability. The ambiguity regarding the criteria for exemptions (exception) in this article has resulted in judges and litigants being unable to interpret its provisions accurately and correctly. This research employs a descriptive-analytical method with a problem-solving approach to critique and examine the shortcomings of this legal article. The research explores potential criteria for the exceptions mentioned by investigating narrative sources and jurisprudential and legal texts. It aims to provide a comprehensive definition to assist judicial authorities in better identifying excluded cases of debt and proposes an innovative approach to identify the customary status of insolvent individuals in terms of their inability to pay judgments using quantitative variables. The research has been investigated by proving the substantive difference and the necessity of distinguishing between the issue of insolvency regarding judicial costs and the common jurisprudential insolvency, the non-application of religious effects that arise for those insolvents from paying judgments to those unable to pay court fees, categorizing these claims as non-judicial. It also evaluates some legal implications, such as resolving the prolongation (proceeding and claim) problem of court cases related to insolvency from court costs and reducing the judicial burden of these claims.